F. J. Mahowald Shoe Shop Interior (Blue Earth County Historical Society 415 Cherry Street, Mankato, MN 56001; http://www.bechshistory.com, 1909)
2f0a8ec432199c015472d50e54c1bef2
F. J. Mahowald Shoe Shop interior; merchandise; Roy Brooks and Frank J. Mahowald.
United States
Minnesota
Blue Earth
Downtown business
Mankato
Mode of access: Internet.
Keywords: Mahowald, F. J., Shoeing Shop; Business and industry